Ekspolarasi Astrofotografi Dalam Pengamatan Bintang Malam Hari Di Pulau Samalona (Studi Penafsiran QS. Al-Mulk Ayat/67:5) - Fauzan, Evand Nur; Alimuddin, Alimuddin (Universitas Islam Negeri Alauddin Makassar, 2026)
Abstract This study discusses astrophotography techniques for nighttime stargazing on Samalona Island. The main problem is how to use astrophotography techniques for nighttime stargazing using a Canon 650D DSLR camera with a 50 mm/Standard 18-55 mm lens and an Apple 13 Pro Max mobile phone, and how to implement QS. Al-Mulk/67:5 for nighttime stargazing on Samalona Island. This type of research is field research with qualitative descriptions that function to identify problems in a structured manner. Field research. The research conducted by the author by collecting several data and direct observations in the field, with the aim of describing astrophotography techniques for nighttime stargazing on Samalona Island (a study of the interpretation of QS. Al-Mulk/67:5). The results of this study are astrophotography techniques using a Canon 650D DSLR camera are certainly very effective in photographing stars and the iPhone 13 Pro Max has been proven to be usable for basic astrophotography, such as photographing constellations, the moon, and bright galaxies (in very dark locations). The implementation of QS. Al-Mulk 67:5 not only describes the beauty of the star-studded sky but also hints at the importance of deeply understanding Allah's creation. In the context of astronomy, this verse provides a theological basis that observing the sky is not merely a scientific activity, but also an act of worship and a form of glorification of the Creator. The implications of this research suggest that the integration of Al-Mulk 67:5, astronomy, and astrophotography can strengthen people's spiritual and scientific awareness of celestial phenomena. Further research is recommended to explore the integration of astrophotography and astronomy in educational activities at madrasahs or Islamic boarding schools (pesantren), as well as to develop structured sky observation programs as a means of da'wah and scientific literacy based on the Quran.